How do dinosaurs say good night? (How do dinosaurs--? (Picture books), , 1, 2008)
Parent and child ponder the different ways a dinosaur can say goodnight, from slamming his tail and pouting to giving a big hug and kiss.

Dragons love tacos (Dragons love tacos, 1, 1, 2012)
Explores the love dragons have for tacos, and the dangers of feeding them anything with spicy salsa!

The book with no pictures (Children's braille book club, ,, 2019)
"In this book with no pictures, the reader has to say every silly word, no matter what"--

Dinosaurs (National Geographic kids readers. Level 1, , 1, 2016)
Introduces dinosaurs, including how scientists know they existed, what they ate, how they cared for their young, and what the descendants of dinosaurs may look like today.
Big scary bones! , Digging up dinosaurs , Dinosaur skin , Big and small , Walking on tip toes , What did dinosaurs eat? , Dinosaur moms and babies , Is that a dinosaur? , Your pet dinosaur.

Pete the cat and the bad banana (Pete the cat easy readers (James Dean), , 1, 2017)
Pete the Cat bites into a bad banana and decides that he never, ever wants to eat bananas again. But Pete really likes bananas! Will one bad banana ruin the whole bunch?

"Slowly, slowly, slowly," said the sloth (Findaway World, LLC, Philomel Books, 2002)
Challenged by the other jungle animals for its seemingly lazy ways, a sloth living in a tree explains the many advantages of his slow and peaceful existence.

The first cat in space ate pizza (First cat in space, 1, 1, 2023)
"Something terrible is happening in the skies! Rats are eating the MOON! There's only ONE hero for the job, a bold and fearsome beast bioengineered in a secret lab to be the moon's savior and Earth's last hope! And that hero is ... a cat. A cat who will be blasted into space! Accompanied by the imperious Moon Queen and LOZ 4000, a toenail clipping robot, the First Cat in Space journeys across a fantastic lunar landscape in a quest to save the world. Will these unlikely heroes save the moon in time? Can a toenail-clipping robot find its purpose in the vast universe? And will the First Cat in Space ever eat some pizza?"--

Narwhal: unicorn of the sea! (Narwhal and Jelly, 1, 1, 2016)
A happy-go-lucky, waffle-loving narwhal and a cynical, no-nonsense jellyfish forge an unlikely friendship and share adventures while exploring the ocean together.
Narwhal is really awesome , Really fun facts , Narwhal's pod of awesomeness , The narwhal song , Narwhal and the best book ever.

Pete the cat and the surprise teacher (Pete the cat easy readers (James Dean), , 1, 2017)
When Pete discovers that his teacher is sick and his mom is the substitute, he must teach her the ins and outs of his school.

The tale of Despereaux: being the story of a mouse, a princess, some soup, and a spool of thread (Listening Library, Findaway World, Random House/Listening Library, Candlewick Press, Books on Tape, Findaway [World, LLC], 2009)
The adventures of Desperaux Tilling, a small mouse of unusual talents, the princess that he loves, the servant girl who longs to be a princess, and a devious rat determined to bring them all to ruin.
A mouse is born , Chiaroscuro , Gor! The tale of miggery sow , Recalled to the light , Coda.

Arthur's tooth (Marc Brown's Arthur adventures, , 1, 1985)
Arthur, tired of being the only one in his class who still has all his baby teeth, waits impatiently for his loose tooth to fall out.

Too many toys (Weston Woods, Findaway World, LLC, Scholastic Inc., Blue Sky Press, Scholastic Audio, 2008)
Spencer has too many toys, but he loves them all! After much haggling, he and his Mom fill a box with toys to give away, but the one toy he can't part with is the box.
Track 1. Story with page-turn signals , Track 2. Story without page-turn signals.

The wild robot (Wild robot, 1, 1, 2019)
When robot Roz opens her eyes for the first time, she discovers that she is all alone on a remote, wild island. She has no idea how she got there or what her purpose is--but she knows she needs to survive. After battling a violent storm and escaping a vicious bear attack, she realizes that her only hope for survival is to adapt to her surroundings and learn from the island's unwelcoming animal inhabitants. As Roz slowly befriends the animals, the island starts to feel like home--until, one day the robot's mysterious past comes back to haunt her.

Splat the Cat and the duck with no quack (Splat the cat (Easy readers), , 1, 2011)
"Splat's bicycle bumps and jumps over the bumpy track on his way to school, until...crack! Splat takes a tumble off of his bike and finds himself nose to beak with a duck. A crash of this caliber should certainly merit some alarm from this duck, but Splat hears no sound. A duck with no quack? Splat thinks that his teacher, Mrs. Wimpydimple, will know what to do, so Splat packs the duck in his backpack along with his school supplies and heads off to Cat School."--Amazon.com.

Too much glue (Flashlight Press, Findaway World, LLC, 2019)
Although Matty's art teacher has warned him that too much glue never dries, Matty loves glue. After all, he and his dad make oodles of glue projects at home. One day during art class, Matty finds the fullest bottles of glue, and the fun begins. With a squeeze and a plop, Matty pours a lake of glue before belly-flopping right in the middle and finds himself stuck to the desk. When Matty's dad arrives at the school, instead of being mad, he celebrates his son's creativity and calls him a work of art.

Bats in the Band (Bat books (Houghton Mifflin Harcourt), , 1, 2014)
When the weather warms up, bats take advantage of an empty theater to stage a concert.

How old is Mr. Tortoise? (Playaway Products, LLC, Abrams Books for Young Readers, OrangeSky Audio, 2023)
It's Mr. Tortoise's birthday and time for cake. But how many candles does the cake need? Mr. Tortoise doesn't remember how old he is so he and the partygoers try various ways to figure his age before they have the cake.

Thank you, Omu! (Little, Brown and Company, Findaway World, LLC, 2019)
When the aroma of Omu's homemade stew fills the air, her neighbors arrive, one by one, for a taste until all is gone except for her generous spirit.

Digger the dinosaur and the Cake mistake (I can read book, ,, 2013)
Today is the big Dino party! Digger and Dadasaur take a ride into town to get a cake, but before long, they end up lost. Can Digger help find the way?

This is MY fort! (Monkey and Cake, 2, 1, 2019)
Monkey and Cake are normally good friends, but today Cake is building a no-Monkey fort--until Monkey teaches him a lesson about being alone and he realizes that forts (and other things) are much better when they are shared.